Raceway-based production of microalgae for possible use in making biodiesel : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biotechnology at Massey University, Palmerston North, New Zealand - Tahir, Sadia (Massey University, 2014)
Oils from microalgae are of interest as a potential feedstock for producing renewable transport fuels including gasoline, diesel, biodiesel and jet fuel. For producing feedstock oils, an alga must be capable of being grown easily in readily available seawater and have a high productivity of biomass and oil. This study explored the biomass and lipid production potential of the microalga Chlorella vulgaris in seawater media, as a potential producer of feedstock oils. The alga was grown photoautotrophically under various conditions in ~2 L Duran bottles and a pilot scale (~138 L) raceway system. Initially, eight species of microalgae of different classes were assessed under nutrient sufficient growth conditions for the production of biomass and lipids in ~2 L Duran bottles. Two of the promising species (C. vulgaris and Nannochloropsis salina) were then further evaluated extensively under various conditions (i.e. salinity stress, different levels of nitrogen in growth media, continuous light and light-dark cycling). Based on these assessments C. vulgaris stood out as the best alga for further detailed study. C. vulgaris was evaluated for biomass production and lipid production. The consumption rates of major nutrients (N and P) were quantified. Biomass was characterized for elemental composition and energy content at the end of the growth cycle. A maximum lipid productivity of ~31 mg L-1 d-1 was attained in Duran bottle batch culture under nitrogen starvation in continuous light with a lipid content in the biomass of 66% (dry weight). This appears to be the highest lipid content reported for C. vulgaris grown in seawater and demonstrates an excellent ability of this alga to accumulate high levels of oil. Under a 12:12 h light-dark cycle, the lipid content and productivity in Duran bottle batch culture were decreased by 13% and 41%, respectively, relative to the case for continuous illumination. Energy content of the biomass produced in Duran bottle batch culture exceeded 30 kJ g-1 both in continuous light and the 12: 12 h light-dark cycle. Batch and continuous culture kinetics of C. vulgaris in the raceway system were assessed. The alga was subjected to various light regimes and nitrogen starvation conditions. Although the N starvation enhanced the lipid accumulation by 42% relative to nutrient sufficient growth in batch culture, the highest biomass and oil productivities were attained under nutrient sufficient conditions in continuous mode of cultivation. Under nutrient sufficiency in continuous culture with a constant illumination of 91 μmol.m-2s-1, the productivities of biomass and lipid in the raceway were >61 mg L-1 d-1 and >8 mg L-1 d-1, respectively. This work represents the first detailed study of C. vulgaris in a raceway pond in full strength seawater media. Previous studies of this alga were almost always carried out in freshwater media.
Keywords: Biodiesel; Microalgae; Chlorella vulgaris; Nannochloropsis salina; Biomass